Youth at Risk in Latin America and the Caribbean : Understanding the Causes, Realizing the Potential - Cunningham, Wendy; McGinnis, Linda; García Verdú, Rodrigo; Tesliuc, Cornelia; Verner, Dorte (Washington, DC : World Bank, 2012)
Realizing the potential of Latin America and the Caribbean's (LAC) youth is essential not only to their well-being, but also to the long-term welfare of the whole region. Young people's families, communities, and governments as well as private, nonprofit, and international organizations, have a responsibility to help youth reach their potential. There have been many successes but also important failures. How to build on the successes and correct the failures is the subject of this report. This book has two objectives: to identify the at-risk youth in LAC, and to provide evidence-based guidance to policy makers in LAC countries that will help them to increase the effectiveness and efficiency of their youth investments. The book concludes that governments can be more effective in preventing young people from engaging in risky behavior in the first place and also in assisting those who already are engaged in negative behavior. To support governments in this endeavor, the book provides a set of tools to inform and guide policy makers as they reform and implement programs for at-risk youth.